Pengaruh Aktivitas Tambang Galian C Terhadap Perubahan Lingkungan Fisik Di Kecamatan Parangloe Kabupaten Gowa - M Riza Pratama; Fadhil Surur (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
In addition to contributing PAD, the excavation mining activities in Gowa have also resulted in various impacts of environmental damage in the form of land subsidence, erosion, deposition (sedimentation), noise, dust and disturbed groundwater levels. This condition not only causes a decrease in the quality of the environment but also has a very serious impact on human health and psyche. This study aims to determine how much influence the c excavation mining activity has on changes in physical environmental conditions and to determine the mining management strategy of the c quarry in Parangloe District, Gowa Regency. The method of data collection was carried out by using field observation techniques, interviews, agency surveys, documentation and literature review methods. The analysis used in this study is multiple regression analysis and SWOT analysis. Based on the results of the analysis, it is found that mining activities affect infrastructure, environmental quality and institutions. Meanwhile, mining activities do not affect the facilities. The quarry management strategy based on the results of the analysis is a strategy that uses strength and takes advantage of opportunities, namely the management of mining C by utilizing local technology and resources in improving the regional economy.